Halal Meat Consumption in East Java: The Role of Employement, Manufacturing, and MSME Income - Marwini, Marwini; Ryandono, Muhamad Nafik Hadi; Wardhana, Akhmad Kusuma; Ali, Mohammad Mahbubi; Dja’akum, Cita Sary (Economica: Jurnal Ekonomi Islam, 2025)
The substantial Muslim population in East Java generates significant demand for halal meat products. Manufacturers and Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in shaping the region’s total halal meat production. This study investigates the influence of the number of workers, manufacturing operating income, and seasonal income of halal meat MSMEs on halal meat consumption in East Java province, Indonesia. Secondary data were collected from seven cities across the province over the period 2003–2022, using a purposive sampling technique. The data were analyzed using a static panel regression model via EViews version 12. The findings reveal that only the variable representing total manufacturing income in the halal meat sector has a statistically significant partial effect on overall halal meat consumption in the selected cities. This suggests that manufacturing enterprises possess distinct advantages over MSMEs in contributing to consumption levels. Conversely, the number of workers in the halal meat sector does not exhibit a significant influence on total meat consumption.